A death long overdue - Gates, Eva, 1951- (Gates, Eva, 1951- Lighthouse library mystery, 2020)
When her former director is found dead in the water, librarian Lucy Richardson will have to get to the bottom of the mystery before the killer ends her tale. It's summertime in the Outer Banks of North Carolina and Bertie James's college class is having their 40th anniversary reunion. The opening night reception is held at the Lighthouse Library and Lucy and her colleagues have assembled an exhibit of library artifacts showing how libraries have changed over the years. After the reception, some of the women take a walk down the boardwalk to the pier, using flashlights to illuminate the dark path, but what's scarier than the dark is finding the former director of the Lighthouse Library floating lifeless in the water. Helena Sanchez, the former director, wasn't much loved and spent the party being rude to almost everyone there. As a result, Lucy finds herself in deep water as she rocks the boat, questioning several suspects. But she'll have to batten down the hatches and fast before she's left high and dry...and right in the killer's crosshairs.